2022
DOI: 10.1111/1744-9987.13832
|View full text |Cite
|
Sign up to set email alerts
|

The association between serum cystatin C and residual renal function in peritoneal dialysis patients

Abstract: Introduction This study evaluated the association between serum cystatin C and residual renal function (RRF) in peritoneal dialysis (PD) patients. Methods The ability of cystatin C to predict RRF was assessed. Multivariate linear regression analysis was conducted to measure the impact of particular factors on serum cystatin C levels. Results The study included 141 PD patients. Serum creatinine and cystatin C were negatively correlated with RRF (p < 0.05). Receiver operating characteristic (ROC) curves showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…Many studies, both in China and other countries, indicated that the levels of serum ALB are inversely correlated with patient mortality, cardiovascular mortality, and technique failure, [19][20][21] because serum ALB is a reactivity index of poor clinical state of severe inflammation, 22 malnutrition, 23 and liver injury. 24 Serum creatinine (Cr) is typically used to estimate glomerular filtration rate and is correlated with residual renal function, 25 which has consistently been an important predictor of improved survival for both HD and PD patients. 26 When we added four variables (diabetes, weight, triglyceride and magnesium), Model 2 became Model 3, the model that had the best predictive efficacy for late technique failure.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies, both in China and other countries, indicated that the levels of serum ALB are inversely correlated with patient mortality, cardiovascular mortality, and technique failure, [19][20][21] because serum ALB is a reactivity index of poor clinical state of severe inflammation, 22 malnutrition, 23 and liver injury. 24 Serum creatinine (Cr) is typically used to estimate glomerular filtration rate and is correlated with residual renal function, 25 which has consistently been an important predictor of improved survival for both HD and PD patients. 26 When we added four variables (diabetes, weight, triglyceride and magnesium), Model 2 became Model 3, the model that had the best predictive efficacy for late technique failure.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, CysC is primarily cleared by residual kidneys, while its PD clearance is very low. Similarly to β2‐MG, serum CysC is also suggested as a useful marker for RKF evaluation [30].…”
Section: Discussionmentioning
confidence: 99%